Potential prognostic implications of whole‐body bone marrow MRI in diffuse large B‐cell lymphoma patients with a negative blind bone marrow biopsy. Issue 6 (14th November 2013) - Adams, Hugo J.A.; Kwee, Thomas C.; Lokhorst, Henk M.; Westerweel, Peter E.; Fijnheer, Rob; Kersten, Marie José; Verkooijen, Helena M.; Stoker, Jaap; Nievelstein, Rutger A.J.
Abstract : Purpose: To assess the prognostic implications of whole‐body bone marrow MRI findings in diffuse large B‐cell lymphoma (DLBCL) patients with a negative blind bone marrow biopsy (BMB). Materials and Methods: Thirty‐eight patients with newly diagnosed DLBCL and negative blind BMB prospectively underwent whole‐body MRI (T1‐weighted, T2‐weighted short inversion time inversion recovery, and diffusion‐weighted sequences), which were scored as positive or negative for lymphomatous bone marrow involvement. Proportions of patients who experienced disease relapse/progression or died during follow‐up were calculated and compared between whole‐body MRI‐positive and whole‐body MRI‐negative patients. Results: The median follow‐up time of surviving patients was 973 days (range, 391–1655 days). Disease relapse/progression occurred in 33% (5/15) of patients with a positive whole‐body MRI and in 13% (3/23) of patients with a negative whole‐body MRI. In addition, 20% (3/15) of patients with a positive whole‐body MRI died during follow‐up, compared with 9% (2/23) of patients with a negative whole‐body MRI. Conclusion: The results of this study show that disease relapse or progression and death may occur more frequently in whole‐body MRI‐positive patients than in whole‐body MRI‐negative patients, which suggests that whole‐body bone marrow MRI findings in DLBCL patients with a negative BMB may have prognostic implications.J. Magn. Reson. Imaging 2014;39:1394–1400 . ©2013 Wiley Periodicals, Inc .